(untitled) (ADMPG Journal, 2025)
This study aims to analyze the influence of effective master data management (MDM) on contemporary organizations. The primary objective is to demonstrate how precise and reliable master data can optimize decision-making, transforming them into accurate and successful choices. Additionally, the theme is explored in depth to show how good master data management can influence the competitiveness of companies, making them more agile, reliable, and consistent. The discussion about the advantages of effective master data management is fostered, revealing various ways to properly manage data. The article also addresses, through practical examples, how a quality master data foundation can provide organizations with a favorable environment for innovation and growth. To this end, some recommendations on how to implement and maintain an MDM system are offered.